Assessment of growth factors with three different platelet preparations, namely platelet-rich fibrin, platelet-rich plasma, and lyophilized platelet: An In vitro study - R Hariprasad; T L Suganya; Serin Sarah John; P Rajesh Raj; Feby kuriakose; V N Anoop (Wolters Kluwer Medknow Publications, 2021)
Assessment of growth factors with three different platelet preparations namely platelet rich fibrin, platelet rich plasma and lyophilized platelet-An invitro study Abstract Enhancing wound healing with patients own blood, particularly the platelet preparations have gained more popularity recently. These platelets excrete large amount of growth factors and cytokines that are associated with the healing process and regeneration. Even though these platelet concentrates are widely used in various forms, the mechanism behind that remains unclear. Therefore, this study aims at investigating the levels of growth factors in three different platelet preparations namely platelet rich plasma (PRP), platelet rich fibrin (PRF) and lyophilized platelets. Materials and Methods Autologous blood for preparing the platelet preparations was obtained from healthy donors aged between 25 to 35 years. The samples were then divided into three experimental groups. The preparation of PRP was done with the addition of anticoagulant and the PRF is prepared without adding it. The platelet counts in the blood were analyzed and the growth factors were quantitatively measured using ELISA reader. The statistical analysis was performed by using the Chi square test. Results In the quantitative analysis of growth factors LPL showed significant increase of the liberation of growth factors compared to PRP and PRF. Conclusions With the various recent advances in technologies for preparing these platelet concentrates this can be widely used in clinical practice more accurate in the future.